School Teachers' Awareness about National Obesity Prevention Programs in Turkey. Issue 5 (3rd September 2019) - Gezmen-Karadağ, Makbule; Yildiran, Hilal; Köksal, Eda; Ertaş Öztürk, Yasemin
ABSTRACT: Nutritional programs are one of the most important public health policies in order to prevent obesity. School teachers are role models for students and their nutrition knowledge about these policies can affect children's dietary habits. The aim of this observational descriptive study was to evaluate the school teachers' awareness about nutrition programs for the prevention of obesity of the Ministry of Education in Turkey. It was conducted to 87, 070 classroom teachers working at state schools from all the cities of Turkey. Data collection was obtained with a plain web-based survey, and national nutrition programs (Nutrition-Friendly School Program, White-Flag Protocol, and circular letter on foods can be sold in school canteens) were questioned. Mean age of teachers was 38.3 ± 9.30 years and 50.4% of them were male. It was determined that only 66.2% of the teachers know whether their school is nutrition-friendly. Frequency of knowing "White-Flag" Protocol was 80.1%. Present study showed that educational programs about nutrition policies are required in order to increase knowledge among school teachers and thus, prevent childhood obesity.